Web-Based Magasing Media to Improve Students' Mathematical Problem-Solving Skills at the Elementary School Level - Putri, Febriyana Retno; Marmuah, Sri; Supianto (Universitas Pendidikan Ganesha, 2024)
Mathematical problem-solving ability is an ability that requires problem solving skills and creativity in solving it because problems in mathematics sometimes require solutions that use creative thinking from students. Through the use of media in mathematics learning, it can help teachers because media is an important component in learning, and from the use of media. Learning activities become more interactive and trigger participant learning motivation which will affect student learning outcomes. The purpose of this study is to analyze the effectiveness of using website-based Magasing media to improve mathematical problem-solving skills so that students can develop their ability to solve complex problems critically. This study used pre-experimental research with a one group experimental design. The sample in this study was 56 students in elementary school. Data collection was done by comparing the results of the pre-test and post-test of the experimental class after being treated using the media. The results of the effectiveness of website-based Magasing media are seen from the results of the pre-test and post test conducted using the paired sample T test. From the results of the research conducted, the pre-test and post test data obtained a result of 56.03 which indicates that the website-based Magasing media is effective in improving students' mathematical problem-solving skills. Based on the results of this study, through the use of website-based Magasing media is effective in improving the mathematical problem-solving skills of students at the elementary school level.